Organizational maintenance for the development of export-oriented enterprise - Xie, Mingxuan (My University, 2024)
The work consists of an introduction, three chapters, conclusions and a list of references, which includes 48 titles, the work contains 5 tables and 2 figures. The volume of the paper is 78 pages. The purpose of the master’s thesis «Adaptation of the company’s development strategy to modern international activity» is to identify and substantiate modern global trends and challenges that affect international business, to determine the necessary adaptations to the existing company strategy and to evaluate the effective framework for strategic modification. In the light of globalization, growing competition in international markets and changes in trade policy, export-oriented enterprises are becoming strategically important for ensuring economic growth, creating new jobs and raising the standard of living of the population. The purpose of the master’s thesis « Organizational maintenance for the development of export-oriented enterprise » is to study the theoretical and methodological aspects of organizational support for the development of exportoriented enterprises, to determine key factors affecting their effectiveness, and to develop recommendations for improving existing organizational structures and business processes in order to increase competitiveness in the international market. According to the goal, the following tasks are outlined: -Analyze the strategic response strategies of domestic and international small and medium-sized manufacturing enterprises during crises; -Assess the market opportunities and challenges for Mingfeng Lighting Co., Ltd. post-pandemic; -Study the strengths and weaknesses of the current development strategy of Mingfeng Lighting Co., Ltd.; -Propose a strategic adjustment plan based on the company’s internal and external environment; -Explore how technological innovation and brand development can enhance the company’s competitiveness; -Analyze the impact of logistics and supply chain management on the implementation of the strategy; -Propose measures to ensure the successful implementation of the company’s strategy. The object of the study is an export-oriented enterprise in the context of their development and organizational support. The subject of the study is a set of theoretical and methodological aspects of organizational support, methods and tools that contribute to the effective development of export-oriented enterprises. The information base of the study is composed of scientific sources, statistics, data from international organisations and international standards, financial and ESG reporting data of Mingfeng Lighting Co., the results of its own research and Internet resources. Scientific novelty of the results: The conclusions and recommendations of the work can help Mingfeng Lighting Co. to successfully implement sustainable development goals in the company’s activities through the expansion of foreign economic activity. The research results were approved at the VII International Scientific and Practical Online Conference: ‘New Challenges for the Agrarian Sector of Ukraine in the Context of Globalisation’ (Kyiv, NUBIP of Ukraine, 9 May 2024). The main provisions and results of the study are reflected in the conference proceedings: MINGXUAN X., IBATULLIN M. ORGANIZATIONAL MAINTENANCE FOR THE DEVELOPMENT OF EXPORT-ORIENTED ENTERPRISE. New challenges for the agricultural sector of Ukraine in the context of globalisation: Proceedings of the VII International Scientific and Practical Conference of Students, Postgraduates and Young Scientists, 9 May 2024 - K.: NUBIP of Ukraine, 2024.
Організаційне забезпечення розвитку експортно-орієнтованого підприємства
Keywords: sustainable development; sustainable business development; foreign economic strategy; foreign economic activity; environmental responsibility; social responsibility